Adaptive compliant controller for space robot stabilization in post-capture phase. (June 2021) - Xia, Pengcheng; Luo, Jianjun; Wang, Mingming
Safety and reliability are the primary prerequisites of space robotic manipulation. Due to the inaccurate inertial parameters of the tumbling target, tracking the desired trajectory directly will lead to the build up of large contact force and torque and damage the grasping point. The measurement noise in the contact wrenches will disturb the application of compliant stabilization strategy, and lead to mission failure. In order to coordinate the desired motion and contact, a compliant stabilization is required for realistic application. However, the measurement noise in the measured contact will disturb the application of compliant control scheme. According to these facts, herein, an adaptive compliant stabilization control scheme is proposed for a safe and reliable stabilization process. With the reference of the unsafe desired motion, a safe admittance motion is generated with an adaptive stiffness virtual spring. In consideration of the parameter selection and the presence of the contact wrenches measurement noise, a neural network-based coordinated adaptive impedance tracking controller is designed to track the safe motion and consume the transmitted energy from the tumbling target at the same time. With the benefit of the combination of the admittance motion and the coordinated adaptive impedance tracking controller, interactions at the grasping point can be controlled and the target can be stabilized under the influence of the measurement noise in the contact wrenches. Furthermore, safety and reliability of the proposed control scheme are validated via digital simulations.